(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The experience of childbirth is beyond the physiological aspects. It has been said that it is more than just a usual day in a woman’s life. This experience influences a woman’s self-confidence, self-esteem, view of life, view of her relationships and view of her children. It can be one of the most influential experiences for a woman1. Although, labour is often thought of as one of the most painful event in human experience, it ranges widely from woman to woman and even from pregnancy to pregnancy. Childbirth is a natural and universal phenomenon, yet the knowledge of it among women is rather haphazard, incomplete and distorted. A woman generally has a vague notion that childbirth is unbearable pain and danger2.